Workshop on Medical Ethics: 28-30 June 1995/29 Muharram-1 Safar 1416 International Islamic University, Islamabad, Pakistan (American Journal of Islam and Society, 1996)
It was indeed an auspicious occasion when experts in different academicfields came together to discuss questions confronting Muslim societybased on recent medical advancements. Many medical doctors, lawyers,and-scholars of Islamic studies met at the International Islamic University,Islamabad, to discuss these matters. Rector Malik Meraj Khalid inauguratedthe workshop. The president and prime minister of Pakistan, FarookAhmad Khan Leghari and Benazir Bhutto, respectively, sent goodwillmessages.The legality of organ transplants and autoposies, as well as the exactdetermination of the actual moment of death, were the main issues of discussion.These issues were analyzed at length in order to determine whetherthere were substantive differences between the approach(es) of medicalspecialists and of Islamic studies specialists.Muhammad Tasin, a prominent Pakistani scholar, delivered thekeynote address: "The Problem of Corneal Transplantation." He examinedthe idea of organ transplantation and organ donation after death and foundthem Islamically permissible. Since the Qur'an and Sunnah contain no cleartexts on these questions, he argued that the problem should be resolvedthrough qiyas (analogy). He also argued that, in the case of genuine necessity,the dissection of corpses was lawful and cited a number of authoritiesto support his opinion. Based on this premise, he declared that cornealtransplants were permissible. He also examined critically the arguments ofscholars who consider autopsies to be unlawful.Tasin refuted the major argwnent of those opposed to transplantation:Since the individual does not own his/ber body, he/she cannot decide howto dispose of it after death. He cited several Qur'anic verses that describethe individual as the owner of his/ber body and wealth. In general, participantswere inclined to support his viewpoint and extend the lawfulness oftransplantation to other human organs. They also generally agreed that anorgan could be donated lawfully by a living individual if the individual'shealth would not be affected adversely.The most vehement opposition came from a medical doctor, RafiqAhmad Ghuncha (assistant professor of anatomy, Armed Forces MedicalCollege, Rawalpindi). He argued forcefully that a doctor's mandate wasconfined to the patient's treatment and not to increasing his/her life span. Insupport, he referred to kidney transplants, which, he said, cost on the aver 284age about Rs 200,000 (roughly $6,250). In the most successful case, atransplanted kidney scarcely survives for more than four or five years.Moreover, after the operation, a further Rps. 6OOo (roughly $US 200) isrequired for medication. Eventually, this means that a middle-class familymust part with the accumulated resources of virtually all of the patient’sclose relatives. In his opinion, moreover, legalizing transplantation wouldencourage trade in human organs, with the result that poor and exploitedsegments of society would be lured into donating their organs in the hopeof augmenting their income. He quoted several incidents to stress that thelegalization of this practice would have disastrous consequences. All participantsagreed that trade in human organs was unlawful ...